Ingresos y egresos del Centro Médico “Carlos Luis Morales Reina” del cantón Babahoyo periodo 2022-2023. - Rodríguez Moran, Miguel Ángel (2025)
The control of income and expenses is a fundamental aspect to ensure the financial sustainability and efficiency of any institution, including medical centres. In this context, the “Carlos Luis Morales Reina” Medical Centre, located in the Babahoyo canton, faces challenges related to the proper management of its financial resources, which directly impacts the quality of services provided to the community. This study aims to evaluate the effectiveness of the institution's income and expense control through a detailed analysis of the financial records for the period 2022-2023. The goal is to identify any potential shortcomings or omissions in the administrative processes that could affect the centre's economic stability. The analysis focuses on reviewing the procedures used for recording and controlling cash flows, comparing current practices with best methodologies in financial management within the healthcare sector. In this way, the study not only identifies areas for improvement but also provides practical recommendations and strategies to optimise resource management, ensuring transparency, efficiency, and long-term viability for the institution. Thus, the study contributes to strengthening the “Carlos Luis Morales Reina” Medical Centre, enhancing its ability to provide quality healthcare in an increasingly challenging economic environment.